ANALISIS PERATURAN PERUNDANGAN-UNDANGAN MENGENAI EKSPANSI PERUSAHAAN GROUP DI SEKTOR PERTAMBANGAN BATUBARA - Hartana (Jurnal Komunikasi Hukum, 2022)
In relation with the coal mining business growth in Indonesia for the past 10 years, than it must also supported with the fulfillment of the applicable Laws, than the purpose of this disertation are, first, the author eagers to know and to find the Laws which specifically regulates the expansion buoying of Group Company especially in coal mining sector. Second, the author eagers to know about the implementation of Group Company expansion in coal mining sector. Third, to know, analyze, and to find the implication of Group Company expansion in mining sector toward monopoly practice and unfair business competition. In this research, the author uses the Juridical Empirical Method, a procedure of solving research problems by first, researching secondary data to continue with the primary data research on field. As for the type of the research are Literature and Field research. The results of this research are, first, that the Law No. 4 Year 2009 regarding Mineral and Coal Mining regulates about the buoying of group company, mentioning that the IUP and IUPK owners are banned from involving their sister company and/or their affiliation in mining service industry located in their mining area, except they have the Minister’s License. Meanwhile maximum area ownership of IUP in group company is not restricted. Second, the most common group expansion in coal mining industry are by establishing holding company, acquisition and joint venture. The principal motive of these actions are economy and psychology. Third, group company expansion in coal mining industry implicates on the growth of new companies and directly implicate the ownership of holding company shares in the sister company. In addition, group company expansion also implicates the business diversification as part of strategic action in order to dominate the upstream and downstream business. Last, group company expansion implicates on the rise of coal production which is at current condition it has not been implicates to monopoly prctice and unfair business competition. The coal production has major role in supporting the National and Regional development.